PENGARUH STRUKTUR MODAL (LEVERAGE), LIKUIDITAS (CR), PROFITABILITAS (ROA), PERTUMBUHAN LABA DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA DI PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Khatarina, Ninta; Situmorang, Sonya Tamara; Sembiring, Desnaria; Pasaribu, Eva Sefti Triyani Lamtiur (2021)
This writing is carried out with the hope of seeing and conducting tests on the capital structure, profitability, liquidity of income growth and business business ratios on the quality of profits in business institutions that run their business in the field of beverages and food listed on the Indonesia Stock Exchange for the 2017-2019 period. This work uses a quantitative analysis technique. The population used is 28 in business institutions that run their business in the field of beverages and food listed on the IDX for the 2017-2019 period. Samples are obtained by purposive sampling method. This method is commonly used by other authors as the sample is taken more towards the purpose of business entities. The sample taken amounted to 15 business institutions. The data analysis used several tests,namely normality test, multicollinearity test, heteroscedasticty test, autocorrelation test, F test and T test. In this study, it was shown that some the capital structure(leverage), liquidity(cr), profitability(roa), the increase in profits and the ratio of business institutions have no significant effect on earnings quality listed on the Inonesia Stock Exchange. together with the financial structure (leverage). Liquidity(cr, profitability(roa), profit growth and compny size also have no significant effect on earings quality in food and beverage sub-sector business institutions contained in BEI.